Geopolymer Concrete Made From Volcanic Ash of Mount Sinabung - Karolina, Rahmi; Sofran, Muhammad Abdany; Handana, M.A.P; Syahrizal,; Siregar, Riza Inanda (International Journal of Integrated Engineering, 2020)
Geopolymer concrete is one of the solutions in an environmentally friendly concrete production process. This research aimed to produce geopolymer concrete from Sinabung volcanic ash, which has high content of SiO2, and to discover the mechanical behavior of the resulted geopolymer concrete. The geopolymer concrete made was in cylindrical shape with diameter of 10 cm and height of 20 cm height. The mixture component consisted of NaOH and Na2SiO3 as alkaline activator. The curing process was conducted in the oven at 60Â°C for four different variation of time, namely, 4 hours, 8 hours, 12 hours and 24 hours. The mechanical properties were measured by testing the compressive strength and absorption value for the sample aged 7-day, whereas the estimated value for 28-day value was calculated from the conversion formula. The tests referred to SNI 1974:2011 testing regulation and ASTM C39 for compressive strength; and ASTM C642 for absorption test. The results showed that for 7-day aged samples, which were cured for 4 hours, 8 hours, 12 hours and 24 hours, obtained the average of compressive strength of 18.54 MPa, 23.85 MPa, 30.65 MPa and 36.75 MPa, respectively. The estimated calculation showed that concrete continued to increase in compressive strength. The 28-day aged samples showed the maximum compressive strength of 58.79 MPa. However, after 28 days, the concrete was projected to start to slow down. The absorption test results of each variation were 2.65% for 4 hours; 1.67% for 8 hours; 1.38% for 12 hours and 0.58% for 24 hours. Based on these results, it can be concluded that the curing time of 24 hours gave the most optimal compressive strength and the smallest value of absorption test. From the compressive strength result, it can be said that the geopolymer concrete made from Sinabung volcanic ash has high quality of concrete.